2017
DOI: 10.1097/ccm.0000000000002077
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of RBC Transfusion Practice in Adult ICUs and the Effect of Restrictive Transfusion Protocols on Routine Care

Abstract: Objective Research supports the efficacy and safety of Restrictive Transfusion Protocols (RTP) to reduce avoidable red blood cell (RBC) transfusions, but evidence of their effectiveness in practice is limited. This study assessed whether admission to an intensive care unit (ICU) with an RTP reduces the likelihood of transfusion for adult patients. Design Observational study using data from the multi-center, cohort Critical Illness Outcomes Study. Patient-level analyses were conducted with RBC transfusion on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
(42 reference statements)
0
11
1
Order By: Relevance
“…Red blood cell (RBC) transfusion remains common, particularly in critically ill patients. [1][2][3] However, transfusion of red cell concentrates (RCCs) is independently associated with increased risks of nosocomial infection, organ dysfunction, and death. [4][5][6] Transfusion-related immunomodulation (TRIM) includes both immunosuppressive and inflammatory effects that may in part explain increased risks in patients who receive blood transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…Red blood cell (RBC) transfusion remains common, particularly in critically ill patients. [1][2][3] However, transfusion of red cell concentrates (RCCs) is independently associated with increased risks of nosocomial infection, organ dysfunction, and death. [4][5][6] Transfusion-related immunomodulation (TRIM) includes both immunosuppressive and inflammatory effects that may in part explain increased risks in patients who receive blood transfusions.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to transfusion guidelines is no exception. In a study by Seitz and colleagues, 42% of 59 intensive care units studied reported having restrictive transfusion policies in place that were in line with current AABB guidelines. However, transfusion rates in patients with a Hb level of 7 g/dL or more were as high as 20%, indicating a substantial lack of compliance with the institutional guidelines.…”
Section: Discussionmentioning
confidence: 98%
“…Various adult ICU protocols are shown to streamline acute care and improve patient safety in multiple ways such as, oral care protocols leading to decreased ventilator-associated pneumonia rates, electrolyte replacement protocols reducing time from abnormal laboratory result to electrolyte normalization, and transfusion guidelines reducing the rate of nonevidencebased transfusions. [17][18][19][20][21] While patients with CCI require individualized care, they also have predictable chronic needs that can be proactively managed with protocols.…”
Section: Discussionmentioning
confidence: 99%